Investigation into the importance of using natural PVCs and pathological models for potential-based ECGI validation - Bear, Laura R.; Bergquist, Jake A.; Abell, Emma; Cochet, Hubert; MacLeod, Rob S.; Dubois, Remi; Serinagaoglu, Yesim (Frontiers in Physiology, 2023)
Introduction: Premature ventricular contractions (PVCs) are one of the most commonly targeted pathologies for ECGI validation, often through ventricular stimulation to mimic the ectopic beat. However, it remains unclear if such stimulated beats faithfully reproduce spontaneously occurring PVCs, particularly in the case of the R-on-T phenomenon. The objective of this study was to determine the differences in ECGI accuracy when reconstructing spontaneous PVCs as compared to ventricular-stimulated beats, and to explore the impact of pathophysiological perturbation on this reconstruction accuracy. Methods: Langendorff-perfused pig hearts (n=3) were suspended in a human torso-shaped tank and local hyperkalemia was induced through perfusion of a high K+ solution (8 mM) into the LAD. Recordings were taken simultaneously from the heart and tank surfaces during ventricular pacing and during spontaneous PVCs (including R-on-T), both at baseline and high K+. Epicardial potentials were reconstructed from torso potentials using ECGI. Results: Spontaneously occurring PVCs were better reconstructed than stimulated beats at baseline in terms of electrogram morphology (Correlation Coefficient, CC= 0.74±0.05 vs CC= 0.60±0.10), potential maps (CC= 0.61±0.06 vs CC= 0.51±0.12), and activation-time maps (CC= 0.86±0.07 vs 0.76±0.10), though there was no difference in the localization error (LE) of epicardial origin (LE= 14±6 vs 15±11 mm). High K+ perfusion reduced the accuracy of ECGI reconstructions in terms of electrogram morphology (CC= 0.68±0.10) and AT maps (CC= 0.70±0.12 and 0.59±0.23 for isolated PVCs and paced beats, respectively. LE trended worse but the change was not significant (LE= 17±9 and 20±12 mm). Spontaneous PVCs were less well when the R-on-T phenomenon occurred and the activation wavefronts encountered a line-of-block. Conclusion: This study demonstrates the differences in ECGI accuracy between spontaneous PVCs and ventricular-paced beats. We also observed a reduction in this accuracy near regions of electrically inactive tissue. These results highlight the need for more physiologically realistic experimental models when evaluating the accuracy of ECGI methods. In particular, reconstruction accuracy needs to be further evaluated in the presence of R-on-T or isolated PVCs particularly when encountering obstacles (functional or anatomical) which cause line of block and reentry.